(untitled) (The Journal of Building and Land Development, 2024)
This paper aimed to enhance understanding of utilisation and production of biogas to meet domestic energy needs in urban areas. BiogasÂ is a renewable fuel produced when microorganisms break down organic matter without oxygen. Each type of organic waste has own biogas production yield depending on the characteristics of the substrate. Methodology used in the study involved an inventory survey, interviews, a pilot plant experimental setup and laboratory analysis. The Biogas pilot plant encompassed 2 reactors, each with a capacity of 1m3. One of the reactors was fed with kitchen waste and the other with 1.5kg of kitchen waste and 40L of raw sewage. Results revealed that households can generate an average of 1.5kg/day and 210L/day of kitchen waste and raw sewage, respectively. The COD for kitchen waste, wastewater and Faecal Sludge were 29,163mg/L, 1930mg/L and 32,970 mg/L, respectively. The householdâ€™s energy cost was established to be about Tshs 166,830/month. It was established 66.7% of the households use both LPG and charcoal for cooking. A combination of kitchen waste and raw sewage can generate about 0.844m3, covering about 84% of the total household energy demand or 130.7% of cooking time (2.81 hrs). The study concludes that household organic waste can generate biogas, reduce energy costs, address energy shortages and protect the environment. Co-digesting of kitchen waste and raw sewage can save up to Tshs 140,371/month on LPG and charcoal. Â Keywords: Kitchen waste, faecal sludge, anaerobic digestion, charcoal, LPG